Bisphosphonate Associated Osteonecrosis of the Jaw: An Update on Pathophysiology, Risk Factors, and Treatment - Lars Rasmusson; Jahan Abtahi (Hindawi Limited, 2014)
Osteonecrosis of the jaw in patients treated with bisphosphonates is a relatively rare but well known complication at maxillofacial units around the world. It has been speculated that the medication, especially long-term i.v. bisphosphonate treatment, could cause sterile necrosis of the jaws. The aim of this narrative review of the literature was to elaborate on the pathological mechanisms behind the condition and also to gather an update on incidence, risk factors, and treatment of bisphosphonate associated osteonecrosis of the jaw. In total, ninety-one articles were reviewed. All were published in internationally recognized journals with referee systems. We can conclude that necrotic lesions in the jaw seem to be following upon exposure of bone, for example, after tooth extractions, while other interventions like implant placement do not increase the risk of osteonecrosis. Since exposure to the bacterial environment in the oral cavity seems essential for the development of necrotic lesions, we believe that the condition is in fact chronic osteomyelitis and should be treated accordingly.